Efficacy of 12 months therapy with glucagon-like peptide-1 receptor agonists liraglutide and semaglutide on weight regain after bariatric surgery: a real-world retrospective observational study - Anders Boisen Jensen; Ursina Machado; Frida Renström; Stefan Aczél; Patrick Folie; Magdalena Biraima-Steinemann; Stefan Bilz (BMC Endocrine Disorders)
Abstract Background The role of glucagon-like peptide-1 receptor agonists (GLP1-RAs) in patients with weight regain after bariatric surgery remains unclear. The objective of this study was to determine the efficacy and safety of 12 months of GLP1-RA treatment in a real-world patient population with weight regain after bariatric surgery. Methods A single-centre retrospective observational study. Patients with post-bariatric weight regain subsequently treated with GLP1-RA were identified, and the effect on weight after 12 months of treatment was determined. Data are presented as medians (interquartile ranges) or frequencies (%), and Wilcoxon signed-rank tests and Mann-Whitney U tests were used for paired and nonpaired group comparisons, respectively. Results Forty patients (80% female) were included in the analysis. Liraglutide (3.0 mg, daily subcutaneous injection, n = 22) or semaglutide (1.0 mg, weekly subcutaneous injection, n = 18) was started 74.5 (51.0, 108.3) months after surgery following a weight regain of 14.7 (10.3, 19.6)%. After 12 months of GLP1-RA treatment, a total body weight, BMI, and percentage excess body weight reduction of 10.5 (6.1, 14.7) kg, 3.7 (2.5, 5.3) kg/m2, and 41.7 (22.1, 70.5)% were observed, corresponding to a loss of 99.3 (61.0, 135.4)% of the weight regained (P-value < 0.0001). The observed reduction in BMI was significantly lower with liraglutide than with semaglutide, 3.1 (2.0, 4.7) vs. 4.7 (3.7, 6.0) kg/m2 (P-value = 0.04). Adverse events were reported in 13 (32.5%) patients, all of which were mild and transient. Conclusion GLP1-RA therapy with liraglutide or semaglutide for 12 months is efficacious and safe for the treatment of weight regain following bariatric surgery. Clinical trial number Not applicable.